2016
DOI: 10.1111/rda.12877
|View full text |Cite
|
Sign up to set email alerts
|

Antisperm antibodies in repeat‐breeding cows: Frequency, detection and validation of threshold levels employing sperm immobilization, sperm agglutination and immunoperoxidase assay

Abstract: Antisperm antibodies have been found in repeat-breeding(RB) cows, and those causing agglutination and/or immobilization of sperm are considered to be closely related to unexplained infertility. However, a standard protocol for identifying antisperm antibodies (ASA) in cattle is not validated. Therefore, an investigation was undertaken to evaluate sperm immobilization (SIT), sperm agglutination (SAT) and immunoperoxidase (IPT)assays for detection of ASA in serum and their respective threshold levels for confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…Research in cattle, which is a relatively close species to deer, demonstrated that the incidences were much higher. Five point eight eight % of heifers, 25.00% of normal breeders, 18.75% of pregnant cows and 59.00% of repeat-breeders were positive in the sperm agglutination test [ 23 ]. Although we did not distinguish the gender and reproductive potential of individual deer, the prevalence was lower than that of fertile humans and domestic animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in cattle, which is a relatively close species to deer, demonstrated that the incidences were much higher. Five point eight eight % of heifers, 25.00% of normal breeders, 18.75% of pregnant cows and 59.00% of repeat-breeders were positive in the sperm agglutination test [ 23 ]. Although we did not distinguish the gender and reproductive potential of individual deer, the prevalence was lower than that of fertile humans and domestic animals.…”
Section: Discussionmentioning
confidence: 99%
“…Antisperm antibodies occasionally emerge without such an active immunization. Repeat-breeding cows are frequently exposed to sperm antigens and produce sperm-reactive antibodies [ 23 ]. Some of the antibodies agglutinate and/or immobilize bull sperm, presumably reducing their fecundities.…”
mentioning
confidence: 99%
“…To set the threshold levels for confirmation of the presence of ASAs in the serum of repeat breeding cows, various assays including the sperm immobilization test, sperm agglutination test, and immunoperoxidase test were carried out (Srivastava et al, ). The study reported the incidence of ASA positivity in female animals in this order: heifer < normal breeder < pregnant animals < repeaters and concluded that the immunoperoxidase test was more specific and accurate in detecting ASA in sera of the animals.…”
Section: Diagnostic Methods To Identify Immune Regulatory Moleculesmentioning
confidence: 99%
“…Though such antigens were not reported in livestock, ASA bound spermatozoa negatively affects the ability of spermatozoa to undergo capacitation and zona binding in bovine (Ferrer et al, ). Immobilization and sperm agglutination were observed in the cervical mucus of repeat breeding cows suffering from idiopathic infertility (Srivastava et al, ). The uterus is primarily an immune‐privileged site during pregnancy, yet reacts differently to various antigens during different phases of the reproductive cycle (Arck, Solano, Walecki, & Meinhardt, ; Clark & Schust, ).…”
Section: Testicular Immune Mechanismmentioning
confidence: 99%
“…In contrast, most antigenic proteins have been documented to have adverse effects on sperm function by generating anti‐sperm antibodies (ASAs) (IgG and IgA) in reproductive tract secretions, the possible cause of immune infertility in males (Archana et al., 2020). The difference in the effect of antigenicity between the functional attributes of fresh and frozen‐thawed spermatozoa could be due to degradation (Meggiolaro et al., 2003) or changes in the antigenic properties of proteins during cryopreservation (Lessard et al., 2000), or due to binding of secretory antibodies to surface antigens causing spermatozoa agglutination (Barbonetti et al., 2019; Srivastava et al., 2017). The ASAs block the sperm capacitation and zona binding by inhibiting the fluidity of the functional membrane (Ferrer et al., 2017) and tyrosine phosphorylation (Pujianto et al., 2018).…”
Section: Sperm Antigenicitymentioning
confidence: 99%